Percepción femenina del trabajo hecho por las mujeres en la vereda Rivera de El Carmen de Viboral, Antioquia (Colombia) (2016)
ABSTRACT: This article shows the way country women perceive the recent transformations of their work in El Carmen de Viboral. This research study employed an ethnographic methodology enhanced with ten life stories of women of different ages in order to delve into their feelings, desires and dreams. We found out than there has been a change in the female activities but this change does not always mean a rise in alterations in perceptions women regarding their gender condition.